2015
DOI: 10.1007/s10616-015-9904-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on expression profile of developmentally important genes during pre-implantation stages in buffalo hand-made cloned embryos derived from adult fibroblasts and amniotic fluid derived stem cells

Abstract: Abnormal gene expression in somatic cell nuclear transfer embryos due to aberrant epigenetic modifications of the donor nucleus may account for much of the observed diminished viability and developmental abnormalities. The present study compared the developmentally important gene expression pattern at 4-cell, 8-to 16-cell, morula, and blastocyst stages of buffalo nuclear transfer (NT) embryos from adult fibroblasts (AFs) and amniotic fluid stem cells (AFSCs). In vitro fertilized embryos were used as control em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Messenger RNA for IGF-2R was already reported in bovine and buffalo embryos (Yaseen et al 2001;Pandey et al 2009;Sadeesh et al 2015Sadeesh et al , 2016. Cultured oocytes from in vitro showed fourfold fewer transcripts of IGF-2R in comparison with in vivo matured oocytes (Katz-Jaffe et al 2009).…”
Section: Discussionmentioning
confidence: 84%
“…Messenger RNA for IGF-2R was already reported in bovine and buffalo embryos (Yaseen et al 2001;Pandey et al 2009;Sadeesh et al 2015Sadeesh et al , 2016. Cultured oocytes from in vitro showed fourfold fewer transcripts of IGF-2R in comparison with in vivo matured oocytes (Katz-Jaffe et al 2009).…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, it is possible that the low level of GLUT-1 expression observed in the present study in undefined media embryos is related to higher levels of apoptotic incidence in these embryos. Pantaleon et al (2001) and Sadeesh et al (2015a) demonstrated the importance of glucose transporters for early embryo development where down-regulation results in decreased cell numbers. Based on our results, we inferred that buffalo embryos could detect and respond to defined and undefined IVC conditions by altering expression levels of GLUT-1, as previously described in bovine (Lim et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, contradictory results have been observed more recently by Kim et al (2012) who described no differences in expression levels of MnSOD between bovine SCNT and IVF embryos. Recently, in buffalo, higher expression of MnSOD has been detected in IVF-derived 8-to 16-cell, morula and blastocyst stage embryos compared with SCNT embryos (Sadeesh et al 2015a). This divergence among experiments may be due to different protocols used to produce and culture embryos or different methods to assess gene expression profile.…”
Section: Discussionmentioning
confidence: 99%
“…Many different determinants have been identified to be related to SCNT efficiency. They encompass (1) cytological and molecular quality of nuclear recipient oocytes characterized by meiotic, cytoplasmic, and epigenomic maturity parameters (Samiec & Skrzyszowska, 2012; Wang et al, 2018; Gupta et al, 2019); (2) the origin and phenotype of nuclear donor cells (Madheshiya et al, 2015; Em et al, 2016); (3) the capability of donor cell nuclear genome to be epigenetically reprogrammed in a cytoplasm of nuclear-transferred oocytes and descendant blastomeres of corresponding cloned embryos (Opiela et al, 2017; Monika & Selokar, 2018; Samiec & Skrzyszowska, 2018 a , 2018 b ; Zhou et al, 2020); (4) molecular and epigenetic communication between nuclear and mitochondrial genomes in nuclear-transferred oocytes and resultant cloned embryos (Hiendleder et al, 2003; Samiec, 2005 a , 2005 b ; Srirattana et al, 2011); (5) the strategies applied to artificially activate embryo-specific developmental programme of nuclear-transferred oocytes (Saikhun et al, 2004; Samiec & Skrzyszowska, 2010, 2014; George et al, 2011); and (6) the frequency of occurrence of apoptosis-dependent events in the in vitro -cultured nuclear donor cells and SCNT-derived embryos (Cui et al, 2011; Samiec et al, 2013; Agrawal et al, 2018; Mehta et al, 2019; Samiec et al, 2019).…”
Section: Introductionmentioning
confidence: 99%